Reproductive period and size at the onset of sexual maturity of mottled purse crab, Persephona mediterranea (Herbst, 1794) (Brachyura, Leucosioidea) on the southeastern Brazilian coast - Bertini, Giovana [UNESP]; Teixeira, Gustavo Monteiro [UNESP]; Fransozo, Vivian [UNESP]; Fransozo, Adilson [UNESP] (Int Science Services/balaban Publishers, 2010)
The reproductive biology of Persephona mediterranea was investigated in relation to the following aspects: population structure, size at the onset of sexual maturity, sexual size dimorphism, and reproductive period. A total of 1,283 specimens were obtained (565 males, 120 non-ovigerous females and 598 ovigerous females). CW(50) values were 22.8 and 22.3 mm CW for males and females, respectively, and the mean size of males was significantly larger than that of females. Persephona mediterranea shows continuous reproduction. However, there is a reduction M the proportion of ovigerous females and males with gonads in advanced developmental stage during the autumn and beginning of the winter. There was no significant correlation between the reproductive activity and variation in abiotic factors. of the total captured specimens, 98.99% were sexually mature, which may indicate a differential spatial distribution among the distinct age groups, and sampling sites are probably areas occupied by adult individuals or this population.
Keywords: Persephona; Population structure; Sexual maturity; Reproduction